From desert margins to global insights: floristic diversity and conservation strategies in the arid regions of Tabuk and Khulais, Saudi Arabia – a bibliometric and ecological synthesis - Al-Mutairi, Khalid Awadh (Frontiers in Forests and Global Change, 2025)
Climate change, hydrological alterations, and anthropogenic pressures are collectively driving rapid ecological shifts in Saudi Arabia’s arid regions, particularly in Tabuk and Khulais. This study evaluates the status and conservation strategies of floristic diversity in these regions through a bibliometric and ecological synthesis. Using bibliometric analysis of 102 selected publications from 1984 to 2025, major thematic clusters were identified, focusing on policy interventions, hydrological impacts, biodiversity loss, and vegetation dynamics. Among these, 20 studies specifically addressed the Tabuk region’s ecological challenges and conservation responses. The findings reveal that rising temperatures (0.70–1.30 °C) and drastic rainfall reduction (up to 85%) have intensified aridity, decreased soil moisture, and accelerated biodiversity degradation. Invasive species such as Prosopis juliflora exacerbate the situation by outcompeting native flora for scarce resources. While rocky ecosystems exhibit resilience due to microclimatic buffering, fragile valley ecosystems require urgent, targeted measures like artificial water input and soil stabilization. Hydrological projects, including dam construction, have yielded mixed outcomes—enhancing species richness in riparian zones while simultaneously disrupting natural seed dispersal and causing habitat fragmentation. Rare and endemic species such as Rheum palaestinum and Astragalus collenettiae serve as vital indicators of ecosystem health and genetic heritage, underscoring the need for species-specific conservation initiatives. The study recommends integrated strategies that combine habitat restoration, sustainable water management, and long-term biodiversity monitoring. Furthermore, ecotourism development and community participation are highlighted as valuable components in achieving conservation goals, aligning with Saudi Arabia’s Vision 2030 and national biodiversity targets. This work contributes a comprehensive framework for managing arid-region floristic diversity under changing climatic conditions. By bridging ecological research with socio-economic and policy dimensions, the study offers valuable insights for sustainable forest and landscape management in desert-margin ecosystems globally.